Baseline Antibody Titre against Salmonella enterica in Healthy Population of Mumbai, Maharashtra, India - Rucha Patki; Sunil Lilani; Dhaneshwar Lanjewar (International Journal of Microbiology)
Objective. The aim of this study was to establish a baseline titre for the population of Mumbai, Maharashtra, India. Method. Four hundred healthy blood donors, attending blood donation camps, were screened using a survey questionnaire. Widal tube agglutination test was performed on the diluted sera (with 0.9% normal saline) of blood donors, with final dilution ranging from 1 : 40 to 1 : 320. Results. Out of 400 individuals providing samples, 78 (19.5%) individuals showed antibody titres ≥ 1 : 40 for at least one antigen and 322 (80.5%) showed no agglutination. The baseline antibody titres against O antigen and H antigen of Salmonella enterica serotype Typhi were found to be 1 : 40 and 1 : 80, respectively. Similarly, the baseline antibody titres for the H antigen of Salmonella enterica serotypes Paratyphi A and Paratyphi B were found to be 1 : 40 and 1 : 80, respectively. Conclusion. Thus, it was noted that the diagnostically significant cutoff of antibody titre from acute phase sample was ≥ 1 : 80 for S. Typhi O antigen and titre of ≥ 1 : 160 for both S. Typhi H antigen and S. Paratyphi BH antigen. Antibody titre of ≥ 1 : 80 can be considered significant for S. Paratyphi AH antigen.